Orthogonally Polarized Green Dual-Wavelength Pr3+:LiLuF4 Laser at 523 and 538 nm with the Power Ratio of 1:1 - Haotian Huang; Yuzhao Li; Yanfei Lü; Nguyentuan Anh; Qian Zhang; Jing Xia (Photonics)
An orthogonally polarized green dual-wavelength (OPGDW) laser output in a Pr3+:LiLuF4 (Pr:LLF) crystal with the power ratio of 1:1 was realized for the first time. We calculated the condition for obtaining the identical power of the two output wavelengths and achieved the OPGDW laser by adjusting the tilt angle of the intracavity etalon and optimizing the output coupling transmittance. Using a frequency-doubled (2ω) optically pumped semiconductor (OPS) laser of 10 W at 479 nm, a continuous wave (CW) OPGDW laser output at 523 nm (π-polarized) and 538 nm (σ-polarized) was achieved with a combined power of 1.83 W. In addition, by type-II critical phase-matched (CPM) β-BaB2O4 (BBO) nonlinear crystal, a 57 mW, 265 nm CW UV laser was also realized by sum-frequency generation (SFG) of 523 nm and 538 nm wavelengths. CW OPGDW lasers with identical power output were ideal for both medical detection and generating UV lasers.